Human papillomavirus and p16 protein expression as prognostic biomarkers in mobile tongue cancer. (3rd October 2017) - Minami, Kazuhiko; Kogashiwa, Yasunao; Ebihara, Yasuhiro; Nakahira, Mitsuhiko; Sugasawa, Masashi; Fujino, Takashi; Yasuda, Masanori
Abstract: Objectives: The objectives were to determine the prevalence of human papillomavirus (HPV) in mobile tongue cancer (MTC) and evaluate associations and survival. Materials and methods: Patients who underwent surgical resection as primary treatment for MTC ( n = 127) were retrospectively evaluated. Formalin-fixed paraffin-embedded (FFPE) specimens were assessed for p16 and p53 by immunohistochemistry; for HPV DNA by nested multiplex polymerase chain reaction (PCR) using two pairs of consensus primers (MY09–MY11 and GP5+–GP6+); and for E6 and E7 oncogenes from 13 high-risk HPV types (16, 18, 31, 33, 35, 39, 45, 52, 56, 58, 59, 66, and 68) by real-time reverse transcription PCR (RT-PCR). Results: There were 18 (14.2%) p16-positive, 45 (35.4%) p53-positive, 9 (7.1%) HPV DNA-positive, and 7 (5.5%) E6 and/or E7 mRNA-positive tumors, but the correlation of all pairs was poor. There was no demographic or histopathologic association with HPV status. Cause-specific survival was significantly better with p16-positive than with p16-negative tumors ( p = .037). Conclusions: The prevalence of HPV and p16 positivity was relatively low and p16 status was a poor surrogate marker for HPV status. The results showed the importance of p16 expression in prognosticating mobile tongue cancer.